Searching for 'pockets of effectiveness' in weak governance states: Preliminary examination of the securities and exchange commission of Myanmar. Issue 2 (15th December 2019) - Soe, Phone Pyae; Lowatcharin, Grichawat; Crumpton, Charles David; Draper, John
Abstract: After decades of military rule, internal conflict, and international isolation, Myanmar has embarked on a course of institution building. In light of Myanmar's low rating on the World Bank's Worldwide Governance Indicators (World Bank Group), the nation faces an enormous challenge in developing public institutions that meet its needs and expectations. This challenge includes development of institutional capacity that will allow Myanmar to participate in international economic affairs. A step in this direction involves the creation of a securities exchange market mechanism. The current study considers the establishment of the Securities and Exchange Commission of Myanmar (SECM) to support securities regulation. It applies a novel organization level of analysis strategy that considers SECM as a 'pocket of effectiveness' (POE) in the context of a low‐performing public institutional setting in terms of the good governance criteria of responsiveness, accountability, and transparency (RAT). While the study finds evidence of progress in building Myanmar's securities regulation, it also finds limits in RAT development that challenges the SECM's potential designation as a 'POE'. Based on feedback from proximate stakeholders in the daily work of the SECM, recommendations are offered for revised policies and practices in order to resolve them. Abstract : This article is the first to examine the Securities and Exchange Commission of Myanmar (SECM) and one of the first to consider Myanmar's institution building. It considers the SECM as a potential 'pocket of effectiveness' by applying the good governance criteria of responsiveness, accountability, and transparency.